Efficacy of zinc–carnosine chelate compound, Polaprezinc, enemas in patients with ulcerative colitis. (February 2014) - Itagaki, Munenori; Saruta, Masayuki; Saijo, Hiroki; Mitobe, Jimi; Arihiro, Seiji; Matsuoka, Mika; Kato, Tomohiro; Ikegami, Masahiro; Tajiri, Hisao
Abstract Objectives. Ulcerative colitis (UC) is a chronic, relapsing and remitting intestinal inflammatory disorder. Zinc is known to be efficacious for the repair of damaged tissue and has been shown to protect against gastric ulceration. This study focused on Polaprezinc (PZ), N-(3-aminopropionyl)-L-histidinato zinc, which accelerates ulcer healing through actions such as prostaglandin-independent cytoprotection and antioxidative activity. Methods. In this randomized, placebo-controlled, investigator-blinded trial, 28 patients with active UC at The Jikei University Hospital were randomly divided into two groups: one treated with a 150 mg PZ enema (n = 18) and the other not treated with a PZ enema (n = 10). All patients received usual induction therapy. Clinical symptoms, endoscopic findings and histological findings were evaluated at entry and one week later. Results. In the PZ group, modified Matts' endoscopic scores were significantly improved after treatment compared to baseline in the rectum (p = 0.004), sigmoid colon (p = 0.03) and descending colon (p = 0.04). In the non-PZ group, scores were not significantly improved in the rectum (p = 0.14) and descending colon (p = 0.34), but were improved in the sigmoid colon (p = 0.04). In the PZ group, the Mayo scores at baseline and at Day 8 were 9.1 ± 1.6 and 5.8 ± 2.7 (p = 0.00004), respectively, and in the placebo group, the scores were 8.9 ± 1.7 and 7.4 ± 2.1 (p = 0.009), respectively. Clinical response or remission was significantly better in the PZ group (71%) than in the placebo group (10%). Conclusions. A zinc-carnosine chelate compound, PZ, enema may become a useful new add-on treatment to accelerate mucosal healing in UC.